2015
DOI: 10.1093/nar/gkv095
|View full text |Cite
|
Sign up to set email alerts
|

Defining the sequence requirements for the positioning of base J in DNA using SMRT sequencing

Abstract: Base J (β-D-glucosyl-hydroxymethyluracil) replaces 1% of T in the Leishmania genome and is only found in telomeric repeats (99%) and in regions where transcription starts and stops. This highly restricted distribution must be co-determined by the thymidine hydroxylases (JBP1 and JBP2) that catalyze the initial step in J synthesis. To determine the DNA sequences recognized by JBP1/2, we used SMRT sequencing of DNA segments inserted into plasmids grown in Leishmania tarentolae. We show that SMRT sequencing recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…within an episome instead of within the genome, DNA sequence specificity of J synthesis is maintained. This was also seen using a similar approach in L. tarentolae [17]. …”
supporting
confidence: 62%
See 1 more Smart Citation
“…within an episome instead of within the genome, DNA sequence specificity of J synthesis is maintained. This was also seen using a similar approach in L. tarentolae [17]. …”
supporting
confidence: 62%
“…It is unclear what determines the specific localization of base J synthesis into specific sequences in the genome. While no consensus sequence or motif is evident from the genome-wide J analysis thus far, it is clear that, for at least the telomeric repeats, there is a sequence specificity component where in the top strand (GGGTTA), only the second T is modified [17, 18]. …”
mentioning
confidence: 99%
“…For any single-molecule, kinetic-based method (ONT, PacBio, Genia), there is an ability to detect epigenetic states, including methyl-cytosine, methyl-6adenosize, and hydroxyl-methyl cytosine, with a potential for detecting a variety of other nucleic acid variants, such as those from DNA damage (e.g., 8-oxo-guanosine). [55][56][57][58][59] Synthetically phased library preparations…”
Section: Natively Phased Library Preparation Methodsmentioning
confidence: 99%
“…From what we know about the mechanism of J biosynthesis, it follows that the highly restricted distribution of J-base must be co-determined by the thymidine hydroxylases (JBP1 and JBP2) that catalyze the initial step in J synthesis. Using SMRT sequencing of DNA segments inserted into plasmids grown in Leishmania 19 , it has been shown that J modification usually occurs near G-rich sequences potentially capable of forming G-quadruplexes and at pairs of Ts on opposite DNA strands, separated by 12 nucleotides. That led Genest et al 19 to propose a model in which JBP2 is responsible for initial J synthesis; then JBP1 binds to pre-existing J and hydroxylates another T that typically resides 13 bp downstream (but not upstream) on the complementary DNA strand.…”
Section: Introductionmentioning
confidence: 99%
“…Using SMRT sequencing of DNA segments inserted into plasmids grown in Leishmania 19 , it has been shown that J modification usually occurs near G-rich sequences potentially capable of forming G-quadruplexes and at pairs of Ts on opposite DNA strands, separated by 12 nucleotides. That led Genest et al 19 to propose a model in which JBP2 is responsible for initial J synthesis; then JBP1 binds to pre-existing J and hydroxylates another T that typically resides 13 bp downstream (but not upstream) on the complementary DNA strand. This model provides a mechanism explaining how JBP1 can maintain existing J following DNA replication.…”
Section: Introductionmentioning
confidence: 99%